Patterns of Acehnese Reduplication in Early Literary Works - Faisal Mustafa (OKARA: Jurnal Bahasa dan Sastra, 2022)
Reduplication is a morphological operation in many Austronesian languages, including Acehnese. This process is very productive in Acehnese, and it occurs with many patterns. This study aims to find out the reduplication patterns in Acehnese based on nine literary works written in the 19th century or earlier. The study also focuses on reduplicated patterns and how affixation is treated in reduplication. The study was qualitative, and thus the data were analyzed qualitatively. The data collection and analysis included data extraction, data classification, data display, and data interpretation. The conclusion was verified by comparing the interpretation and tokens from the data. The results showed that reduplication in Acehnese appeared in total reduplication and partial reduplication. Each pattern involved rhythmic reduplications where vowel and some consonant alterations appeared in the reduplicants. In addition, some of those patterns were lexicalized reduplication, where the reduplication did not have any stem or non-reduplicated form. More than half of the lexicalized reduplicated words were onomatopoeia, words imitating sounds. Finally, only prefixes meu-, peu-, and teu- are found in Acehnese reduplication. These findings have provided comprehensive information regarding the patterns of Acehnese reduplication, which revealed that reduplication is a significant process of word formation in the language.